Evaluasi Program Peningkatan Penanaman Hijauan Pakan Ternak Menggunakan Analytical Hierarchy Process: Evaluation of Forage Cultivation Improvement Program Using Analytical Hierarchy Process - Satwika, Prawesa; Abdullah, Luki; Kumalasari, Nur Rochmah (Departemen Ilmu Nutrisi dan Teknologi Pakan Fakultas Peternakan Institut Pertanian Bogor, 2023)
ABSTRACT The purposes of this research were to evaluate the effectiveness of the forage planting program in achieving the objectives and to formulate a strategy for the development of the forage program. Primary data were obtained through direct observation in the field and filling out a list of questionnaires by the resource persons. The process of collecting data for the evaluation of the forage planting program was carried out in six provinces, i.e., the provinces of Lampung, Central Java, West Nusa Tenggara, South Sulawesi, South Kalimantan and West Papua (purposive sampling). Data analysis was carried out through the analytical hierarchy process (AHP), which was a functional hierarchy, with the main input being human perception. The number of sources for the AHP method was 22 sources consisting of heads of the Directorate of Feed, agencies in charge of animal husbandry in provinces and districts, as well as farmers group. It could be concluded that that the actor that ranks first in the strategy for developing the forage planting program was the farmers group, followed by the district, provincial and central government. The most influencing factor in the strategy for developing a forage planting program was land, followed by climate, production inputs, regional commitment and forage cultivation. The strategy considered important in the development of forage planting programs was forage planting in the rainy season. The results of AHP analysis on the most influential actors and factors, farmers group and land, could be used as a reference for policy makers in developing strategies for developing forage planting programs. Key words: analytical hierarchy process, cattle, evaluation, feed, forage